Development of Learning Videos on Vibration, Waves, and Sounds Material at Junior High Schools based on Local Wisdom of Gamelan Lumajang - Dinar Maftukh Fajar; Alif Mardiana; Rafiatul Hasanah (Universitas Islam Negeri (UIN) Mataram, 2023)
One of the local wisdoms in Lumajang, East Java, Indonesia, namely the Gamelan musical instrument used to accompany Lumajang's typical performances such as Jaran Kencak, Jaran Slining, Ludruk, and so on, has a similar context with junior high school science material, namely Vibrations, Waves, and Sound. Therefore, a learning video for Vibrations, Waves, and Sound based on Lumajang's local wisdom was developed to introduce Lumajang culture to students. The objectives of this study are to describe (1) the validity of and (2) students' responses to the learning video on Vibrations, Waves, and Sound based on the local wisdom of Gamelan Lumajang. This study applies the 4-D development model (Define, Design, Develop, and Disseminate), where the dissemination stage is not executed. The learning video was validated by three experts (material expert, media expert, and teacher as a practitioner) and responded to by 36 junior high school students from the Lumajang district. The video is 31 minutes long, was created with Wondershare Filmora, and was uploaded via YouTube. The results showed that (1) This video met the criteria for material assessment, media assessment, and practicality assessment of 95%, 95%, and 91%, respectively, so it was declared very valid. (2) Descriptions of student responses to the learning video have been explained as a pie chart with the most comments, including engaging, making learning more manageable, and adding insight into Lumajang local wisdom.